(untitled) (El Hilo de la Fabula, 2010)
Borges and the theme of the double. Presence of the theme in stories and poems. Borges’s preference for Robert Louis Stevenson. The double and the mirror. Borges and Whitman. Two kinds of double, the traditional one, or doppelgänger, and the coexistence, or compenetration, of two authors, in this case Borges and Whitman